The Effect of Work Motivation and Discipline on Employee Performance: Study at a company engaged in telecommunications in Bandung - Arlando, Abraham Dwi; Hardiyana, Aan; Kadir, Kadir; Coenraad, Dhea Perdana (Acman: Accounting and Management Journal, 2023)
This study intends to look into and assess how motivation and work ethics affect employee performance at one of Bandung's technology, information, and communication enterprises. Path analysis is the research methodology employed since this study aims to understand how employee performance is related to motivation and work ethic. Additionally, it seeks to comprehend the link structure and the impact of predetermined research variables. According to the research's findings, motivation greatly influences employee performance. Workplace discipline has a significant impact on how well employees perform. Motivation and work discipline significantly impact how healthy employees perform at one of the businesses in Bandung's telecommunications sector. According to the study's findings, one of the companies in Bandung's telecommunications industry has motivated and disciplined employees who are moving in the right direction.